Mesoporous Spheres: Multimetallic Mesoporous Spheres Through Surfactant‐Directed Synthesis (Adv. Sci. 8/2015). Issue 8 (August 2015) - Jiang, Bo; Li, Cuiling; Imura, Masataka; Tang, Jing; Yamauchi, Yusuke
<x xml:space="preserve">Abstract</x> A mesoporous structure is very effective in improving electrochemical activity, owing to its high surface area, abundant active sites and accessible pores. In article number 1500112, C. Li, Y. Yamauchi, and co‐workers synthesize Pt‐based 'multi‐metallic' mesoporous spheres to drastically enhance the electrochemical activity towards methanol oxidation reaction. Because of the high surface area and large‐sized mesopores, these mesoporous spheres exhibit enhanced electrochemical activity.